National Education Strategy at TMI Al-Amien Prenduan - Muru'atul Afifah; Syafa’atus Sholihah Al-Fadhilah (Penerbit Hellow Pustaka, 2024)
The role of education is very influential in efforts to unite the nation so that it maintains insight and awareness of statehood and nationality, attitudes and behavior of love for the country. The TMI Putri Al-Amien Prenduan Islamic Boarding School provides female students not only with religious education but also provides female students with the nationalist education needed in their lives. One of the efforts made by this school is the existence of a national education strategy. In this research, researchers used a descriptive qualitative research approach. The methods used in this research are observation, interviews and documentation. Data sources were obtained from several female students, administrators, female teachers, and senior teachers. Forms of national education strategy include cultivating awareness and the value of love for the nation, holding activities that can foster love for the homeland, studying Islamic religion, getting into the habit of loving domestic products. The supporting factors in the national education strategy are the enthusiasm and enthusiasm of the students, the creativity of the students in their work and the habit of living together in the boarding school. In fact, the inhibiting factor is the attitude of ignorance within the students.